Joy of Missing Out (JOMO): Developing a Multi-Factorial Scale for the FOMO Antithesis in Filipino Emerging Adults (American Journal of Human Psychology, 2025)
The social media’s recent growth has brought about a constant need for engagement which led people to Fear Of Missing Out (FOMO). In line with this, a novel concept, which is the Joy of Missing Out (JOMO), has emerged. JOMO encourages people to embrace solitude, prioritize self-care, and enjoy both online and physical disconnection. Given the increasing relevance of JOMO in the modern age, this study aims to develop a scale that measures its multidimensional aspects. For the first step of the development, the study employed a quantitative research design utilizing Exploratory Factor Analysis (EFA). An 83-item questionnaire, having a 7-point Likert scale, was constructed and distributed to 520 emerging adults (ages 18-30) residing in the province of Davao del Sur. A Shapiro-Wilk test was conducted, and results showed that the data is not normally distributed (p < 0.001). Thus, the Principal Axis Factoring (PAF) was used for factor extraction. Results revealed a five-factor structure which consists of Mindfulness (14 items), Social Media Usage (17 items), Contentment of Solitude (15 items), Social Detachment (5 items), and Social Comparison (5 items). Meanwhile, the Kaiser-Meyer-Olkin (KMO) value of .974 and a significant Bartlett’s Test (p < 0.001) confirmed sampling adequacy. The final scale demonstrated a satisfactory internal consistency (α = .978). Aside from the methodological findings, results also highlighted that mindful individuals who embrace solitude often experience JOMO, while those stuck in social comparison and social media use have a hard time attaining this state. It is recommended to conduct further studies on JOMO in various settings and age groups to raise the findings’ generalizability. It is also recommended to conduct a Confirmatory Factor Analysis to fortify the results of this study.